2013
DOI: 10.20344/amp.4248
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia Radiológica da Disfunção Erétil Arteriogénica: Uma Abordagem Sistematizada

Abstract: Introdução: A disfunção erétil é uma doença com elevada prevalência existindo crescente interesse na sua terapêutica endovascular. Devido à complexidade do sistema arterial pélvico masculino, o conhecimento anatómico é fundamental. Avaliou-se a aplicabilidade da classificação de Yamaki na avaliação de doentes com disfunção erétil arteriogénica usando a Angiografia Tomográfica Computorizada e a Angiografia Digital de Subtração.Métodos: Análise retrospetiva dos achados imagiológicos de Angiografia Tomográfica Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Group D: The internal iliac artery divides into the common trunk for the superior gluteal and internal pudendal arteries and the inferior gluteal artery [58]. The presented results are based on 4 of the included studies [4,30,43,58]. LCI -lower confidence interval; HCI -higher confidence interval; Q -Cochran's Q.…”
Section: Article Information and Declarationsmentioning
confidence: 99%
“…Group D: The internal iliac artery divides into the common trunk for the superior gluteal and internal pudendal arteries and the inferior gluteal artery [58]. The presented results are based on 4 of the included studies [4,30,43,58]. LCI -lower confidence interval; HCI -higher confidence interval; Q -Cochran's Q.…”
Section: Article Information and Declarationsmentioning
confidence: 99%
“…Miner et al (Miner et al, 2012) showed that vasogenic ED preceded coronary heart disease in younger ED patients. The pathology of arterial ED is Frontiers in Physiology frontiersin.org atherosclerosis of the internal pudendal artery, which prevents the corpus cavernosa from receiving sufficient blood flow to achieve erectile status (Pereira et al, 2013). Studies have shown that as vascular smooth muscle cells proliferate, collagen and fibrosis increase, leading to the thickening of the vessel wall and narrowing of the lumen.…”
Section: Vasogenic Edmentioning
confidence: 99%
“…The value of routinely assessing the vascular supply of the phallus of ED patients, in which the other nonvascular causes have been ruled out, cannot be downplayed. [ 3 10 11 12 ] Erectile function is an important lawsuit discussed for cases of divorce, rape, and damages in some clime, especially the Indian subcontinent. [ 10 13 ] Lawyers and their clients often hide under the guise of ED in lawsuits concerning these cases; hence, Doppler evaluation at this point is of immense significance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 10 11 12 ] Erectile function is an important lawsuit discussed for cases of divorce, rape, and damages in some clime, especially the Indian subcontinent. [ 10 13 ] Lawyers and their clients often hide under the guise of ED in lawsuits concerning these cases; hence, Doppler evaluation at this point is of immense significance. Doppler ultrasound is a cheap, minimally invasive, highly sensitive, and specific means of assessing patients with ED.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation